LEAF ANATOMICAL ADAPTATION OF EXOTIC INVASIVE MICONIA CRENATA (VAHL.) MICHELANG ALONG ALTITUDINAL GRADIENT: A CASE STUDY OF MOUNT GEDE PANGRANGO NATIONAL PARK, WEST JAVA, INDONESIA - DECKY INDRAWAN JUNAEDI; EKA FATMAWATI TIHURUA; WIDOYANTI WIDOYANTI; DEDEN GIRMANSYAH (Research Center for Biology, 2024)
Miconia crenata is a widely spread species that occurs in multiple ecosystems. However, there is limited information on M. crenata invasion biology, ecology, and anatomy, particularly in the context of mountainous tropical forest and biodiversity management. Therefore, we examined elevation effects upon leaf anatomical structure of exotic invasive M. crenata at Mount Gede-Pangrango National Park (MGPNP). We sampled the leaves at four different elevations i.e., 715 m asl, 800 m asl, 900 m asl, and 1,000 m asl. Cross section leaf anatomy specimens of M. crenata were obtained by using paraffin method and stained with safranin and fast green. This study found that M. crenata leaf anatomy was correlated with elevation shown by changes in leaf tissue thickness and stomata size. Further study is needed of leaf anatomical variation of exotic invasive species along driven by soil properties and the variation across different plant taxa and growth forms. Such studies are important to determine adaptation capacity of invasiveness.